Answer:
[tex]2x + 4 (x-1) = 2 + 4x[/tex] has one solution
[tex]25 - x = 15 - (3x + 10)[/tex] has One Solution
[tex]4x = 2x + 2x + 5 (x-x)[/tex] has Infinite Solution
Step-by-step explanation:
There are 3 Solutions Given
1) [tex]2x + 4 (x-1) = 2 + 4x[/tex]
2) [tex]25 - x = 15 - (3x + 10)[/tex]
3) [tex]4x = 2x + 2x + 5 (x-x)[/tex]
Solving for each equation separately
[tex]2x + 4 (x-1) = 2 + 4x\\2x + 4x -4 = 2 + 4x\\6x-4=2+4x\\6x-4x=2+4\\2x =6\\x= \frac{6}{2} \\x= 3[/tex]
Hence we conclude that it has one solution.
[tex]25 - x = 15 - (3x + 10)\\25 - x = 15 -3x - 10)\\25 -x =5-3x\\-x+3x=5-25\\2x=-20\\x= \frac{-20}{2} \\x=-10[/tex]
Hence we conclude that it has one solution.
[tex]4x = 2x + 2x + 5 (x-x)\\4x = 4x + 5x-5x\\4x = 4x [/tex]
Hence we conclude that it has Infinite Solutions.